2021
DOI: 10.1186/s12891-021-04360-z
|View full text |Cite
|
Sign up to set email alerts
|

Changes in macrophage and inflammatory cytokine expressions during fracture healing in an ovariectomized mice model

Abstract: Background Macrophages and inflammatory cytokines play important roles in bone fracture healing. However, the expression patterns of macrophages and inflammatory cytokines during fracture healing under the condition of postmenopausal osteoporosis have not been fully revealed. Methods Tibia transverse fracture was established 12 weeks after ovariectomy or sham operation in 16-week old female mice. Tibias were harvested before fracture or 1, 3, 5, 7,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Similar findings were reported in a study by Chen et al (62), in a mouse model of postmenopausal osteoporosis, a condition in which delayed fracture healing is also frequently observed. The authors found that both endochondral ossification and callus remodeling were impaired in ovariectomized mice (OVX), which possessed a decreased expression of TNF-α and IL-6 and a lower frequency of M1 and M2 macrophages in the fracture hematoma, respectively, on days 1 and 14 after the fracture (62).…”
Section: Relationship Of Macrophages and Fracture Impairment In The C...supporting
confidence: 91%
“…Similar findings were reported in a study by Chen et al (62), in a mouse model of postmenopausal osteoporosis, a condition in which delayed fracture healing is also frequently observed. The authors found that both endochondral ossification and callus remodeling were impaired in ovariectomized mice (OVX), which possessed a decreased expression of TNF-α and IL-6 and a lower frequency of M1 and M2 macrophages in the fracture hematoma, respectively, on days 1 and 14 after the fracture (62).…”
Section: Relationship Of Macrophages and Fracture Impairment In The C...supporting
confidence: 91%
“…Activation patterns of the FOSL2 regulon might indicate that skeleton-endocrine functions of FOSL2 are performed predominantly by preosteoblast-S1. Previous studies showed that interactions of FOSL2 and proinflammatory cytokines, including IL-6, contributed to various inflammatory reactions [ 41 43 ]. In addition, FOSL2 regulon’s target gene, IL-6, was included in the core gene modules of immunity-related PPI networks.…”
Section: Discussionmentioning
confidence: 99%
“… 33 In mice, the level of IL-6 reached the peak at 24h after fracture. 34 IL-6 gene is located on chromosome 7q21.3 and contains 5 exons and 4 introns. At present, its common promoter regions SNPs included rs1800796, rs1800795, rs1800797, and rs10499563.…”
Section: Discussionmentioning
confidence: 99%